ECO-BALANCING OF ARABLE FARMING AS A FIRST STEP TO ORGANIC MANUFACTURING OF PLANT GROWING PRODUCTS - Pysarenko, V. M.; Kovalenko, N. P.; Pospielova, G. D.; Pischalenko М. А.; Melnychuk, V. V.; Sherstiuk, E. L. (Scientific Progress & Innovations, 2020)
Preservation of land resources under their active management and mass manifestation of land degradation processes, upsetting soil cover integrity, is now an extremely topical problem, which requires solving. The world practice shows that the prospects of using organic farming in its “pure state” turn out rather limited because of different reasons. At the same time, it is necessary to create certain economic, social and cultural preconditions, and also a rather high level of scientific and technical basis and theoretical knowledge, which are the most important parts in this process, on the territory of different countries of the world and Ukraine. In this connection, the purpose of the article is describing some agro-technical measures, which ensure eco-balancing of arable farming while manufacturing plant growing products. Data have been presented in the paper concerning methods and agro-technical techniques based on many-year observations of crop cultivation (2012–2019) in organic crop rotation at private enterprise “Agroecology” in Shyshaky district, Poltava region. These data can be used in modern farming conditions with the aim of obtaining ecologically safe plant growing products and eco-balancing of arable farming on the whole. Measures aimed at eco-balancing of crop farming while cultivating certain crops, such as: winter wheat, spring barley, corn grain, soybean, pea, sugar beet, rape, sunflower, millet, and buckwheat have been elucidated. Different techniques and measures for each separate crop have been described, and they are connected with: choosing proceeding crops; peculiarities of sowing material treatment with different preparations ensuring better germination, increasing yield or protecting against diseases of different etiology; peculiarities of sowing and further agro-technological cultivation and finally, harvesting. At the same time, different variants have been suggested in the paper as to decreasing or eliminating weed infestation on sown areas and also helping to fight mouse-like rodents and insects – grain crops’pests. Thus, the presented data have both theoretical and practical value for specialists introducing eco-balancing of arable farming, as these data help solve important problems.